Shaping ability of Reciproc and TF Adaptive systems in severely curved canals of rapid microCT-based prototyping molar replicas - Ronald ORDINOLA-ZAPATA; Clovis Monteiro BRAMANTE; Marco Antonio Húngaro DUARTE; Bruno Cavalini CAVENAGO; David JARAMILLO; Marco Aurélio VERSIANI (University of São Paulo, 2014)
Objective: To evaluate the shaping ability of Reciproc and Twisted-File Adaptive systems in rapid prototyping replicas. Material and Methods: Two mandibular molars showing S-shaped and 62-degree curvatures in the mesial root were scanned by using a microcomputed tomography (μCT) system. The data were exported in the stereolitograhic format and 20 samples of each molar were printed at 16 µm resolution. The mesial canals of 10 replicas of each specimen were prepared with each system. Transportation was measured by overlapping radiographs taken before and after preparation and resin thickness after instrumentation was measured by μCT. Results: Both systems maintained the original shape of the apical third in both anatomies (P>0.05). Overall, considering the resin thickness in the 62-degree replicas, no statistical difference was found between the systems (P>0.05). In the S-shaped curvature replica, Reciproc significantly decreased the thickness of the resin walls in comparison with TF Adaptive. Conclusions: The evaluated systems were able to maintain the original shape at the apical third of severely curved mesial canals of molar replicas.